Analysis Of Tourism Development Potential In Physical Planning Of Batutulis Area As Historical And Cultural Tourist Destination In Bogor City - Sunantoputri, Siti Yasmin Salsabila; Rainanto, Bambang Hengky; Saragi, Charles Parnauli (Jurnal Ilmiah Pariwisata Kesatuan, 2024)
The city of Bogor is one of the cities that has large and diverse historical and cultural tourism resource potential, one of which is the Batutulis area. The Batutulis area has historical and cultural tourism potential that can be developed. However, this condition experiences problems which are limited by the identification of scattered sites, congestion, and inadequate infrastructure so that its development requires appropriate strategies such as developing physical planning. Physical planning is planning physical conditions or planning visible resource components such as buildings, roads and other facilities, in order to create a physical environment that is functional, comfortable, safe and attractive. This research uses a qualitative descriptive method with SWOT analysis carried out by observation, interviews and documentation. The sources in this research were the Public Works Department, Transportation Department, Environmental Department, Tourism and Culture Department, South Bogor District, Batutulis Subdistrict and Lawanggintung Subdistrict. Research on the Batutulis area of Bogor City resulted in the conclusion that the tourism potential in physical planning in the area is feasible and has the potential to be developed. This research produces physical planning strategies in the Batutulis area in the form of building tourist facilities, building tourist facilities and infrastructure, developing and managing tourist attractions, as well as developing historical and cultural tourism infrastructure. Keyword: Tourism Development Potential, Physical Planning, Historical and Cultural Tourist Destination, Batutulis Area, Bogor City